Cxs and Panx- hemichannels in peripheral and central chemosensing in mammals - Reyes, Edison Pablo; Cerpa, Verónica; Corvalán, Liliana; Retamal, Mauricio Antonio (Frontiers in Cellular Neuroscience, 2014)
Connexins (Cxs) and Pannexins (Panx) form hemichannels at the plasma membrane of animals. Despite their low open probability under physiological conditions, these hemichannels release signaling molecules (i.e., ATP, Glutamate, PGE2) to the extracellular space, thus subserving several important physiological processes. Oxygen and CO2 sensing are fundamental to the normal functioning of vertebrate organisms. Fluctuations in blood PO2, PCO2 and pH are sensed at the carotid bifurcations of adult mammals by glomus cells of the carotid bodies. Likewise, changes in pH and/or PCO2 of cerebrospinal fluid are sensed by central chemoreceptors, a group of specialized neurones distributed in the ventrolateral medulla (VLM), raphe nuclei, and some other brainstem areas. After many years of research, the molecular mechanisms involved in chemosensing process are not completely understood. This manuscript will review data regarding relationships between chemosensitive cells and the expression of channels formed by Cxs and Panx, with special emphasis on hemichannels.